“Preeclampsia.com” App To Preeclampsia Screening At Community Level: A Cohort Study - Johariyah Johariyah; Detty Siti Nurdiati; Widyawati Widyawati (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
Indonesian maternal mortality in 2012, 32.5% was caused by hypertension, preeclampsia, and eclampsia, while 24.22% in 2015 and 26% in 2016. Currently, there is no method of screening for preeclampsia based on maternal characteristics that were carried out during the first visit antenatal. The use of technology has great potential to improve health care at the community, especially in low-middle income countries. It is necessary to make a breakthrough in the form of developing a screening model for preeclampsia by utilizing information technology. This study aims to determine the detection rate of the application of preeclampsia.com as a community-based preeclampsia screening tool. This study was conducted by cohort study on 549 pregnant women who had their first antenatal visit before 16 weeks followed up to delivery. Data analysis was data of factors for the occurrence of preeclampsia using Chi square, while to determine the strength of the “Preeclampsia.com” model as a screening method and early detection of preeclampsia using multilevel logistic regression, analysis performed using SPSS version 23.0. The results of the analysis showed that the sensitivity value of the